Data management support pack - Abreu, David; Mwanzia, Leroy; Barahona, Carlos; Mills, Dave; Garlick, Cathy; Tobon, Hector (2018)
This pack is designed to help you produce high quality, reusable and open data from your research activities. It consists of documents, templates and videos covering the different aspects of data management and ranging from the overarching concepts and strategies through to the day-to-day activities. For each of the videos in the pack we have included a transcript of the narrative. The Data Management Support Pack was created to support the implementation of the CCAFS Data Management strategy.